Sleep drive is coupled to tissue damage via shedding of Caenorhabditis elegans EGFR ligand SISS-1 - Andrew J. Hill; Bryan Robinson; Jesse G. Jones; Paul W. Sternberg; Cheryl Van Buskirk (Nature Communications)
Abstract The benefits of sleep extend beyond the nervous system. Peripheral tissues impact sleep regulation, and increased sleep is observed in response to damaging conditions, even those that selectively affect non-neuronal cells. However, the ‘sleep need’ signal released by stressed tissues is not known. Sleep in the nematode C. elegans is independent of circadian cues and can be triggered rapidly by damaging conditions. This stress-induced sleep is mediated by neurons that require the Epidermal Growth Factor Receptor (EGFR) for their sleep-promoting function, but the only known C. elegans EGFR ligand, LIN-3, is not required for sleep. Here we describe SISS-1 (stress-induced sleepless), an EGF family ligand that is required for stress-induced sleep. We show that SISS-1 overexpression induces sleep in an EGFR-dependent, sleep neuron-dependent manner. We find that SISS-1 undergoes stress-responsive shedding by the ADM-4/ADAM17 metalloprotease, and that the ADM-4 site of action depends on the tissue specificity of the stressor. Our findings support a model in which SISS-1 is released from damaged tissues to activate EGFR in sleep neurons, identifying a molecular link between cellular stress and organismal sleep drive. Our data also point to a mechanism insulating this sleep signal from EGFR-mediated signaling during development.